Does education prevent job loss during downturns? Evidence from exogenous schools assignments and COVID-19 in Barbados - Diether W. Beuermann; Nicolas L. Bottan; Bridget Hoffmann; Clement Jackson; Diego Alejandro Vera Cossío (Inter-American Development Bank (IDB), 2021)
Canonical human capital theories posit that education, by enhancing worker skills, reduces the likelihood that a worker will be laid-off during times of economic change. Yet, this has not been demonstrated causally. We link administrative education records from 1987 through 2002 to nationally representative surveys conducted before and after the onset of COVID-19 in Barbados to explore the causal impact of improved education on job loss during this period. Using a regression discontinuity (RD) design, Beuermann and Jackson (2020) show that females (but not males) who score just above the admission threshold for more selective schools in Barbados attain more years of education than those that scored just below (essentially holding initial ability fixed). Here, in follow-up data, we show that these same females (but not males) are much less likely to have lost a job after the onset of COVID-19. We show that these effects are not driven by sectoral changes, or changes in labor supply. Because employers observe incumbent worker productivity, these patterns are inconsistent with pure education signaling, and they suggest that education enhances worker skill.
Keywords: I20; J0; 330; Education; Covid-19; Human Capital; Gender; Barbados